2016
DOI: 10.1002/cbic.201600254
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐Templated Introduction of an Aldehyde Handle in Proteins

Abstract: Many medical and biotechnological applications rely on protein labeling, but a key challenge is the production of homogeneous and site-specific conjugates. This can rarely be achieved by simple residue-specific random labeling, but generally requires genetic engineering. Using site-selective DNA-templated reductive amination, we created DNA-protein conjugates with control over labeling stoichiometry and without genetic engineering. A guiding DNA strand with a metal-binding functionality facilitates site-select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
52
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 34 publications
0
52
0
Order By: Relevance
“…We have shown that an aldehyde handle can be concealed during protein conjugation using a 1,2‐diol cleavable linker . The 1,2‐diol linker is cleaved rapidly (1 h) by using 1 m m NaIO 4 under slightly acidic conditions (NaOAc buffer 100 m m , pH 5.5).…”
Section: Label‐containing Moietymentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that an aldehyde handle can be concealed during protein conjugation using a 1,2‐diol cleavable linker . The 1,2‐diol linker is cleaved rapidly (1 h) by using 1 m m NaIO 4 under slightly acidic conditions (NaOAc buffer 100 m m , pH 5.5).…”
Section: Label‐containing Moietymentioning
confidence: 99%
“…In our studies, the concealed handle strategy allowed us to utilize the affinity motifs for purification of the modified proteins, which is nearly impossible in the direct handle‐transfer methods. Afterwards, the cleavable linker allowed removal of the affinity motifs leaving only the small reactive scar …”
Section: Label‐containing Moietymentioning
confidence: 99%
“…In previous work from our group, a tris nitrilotriacetic acid (NTA)‐modified oligonucleotide (ODN) was used for DNA‐templated reactions toward metal‐binding proteins. The tris NTA group showed very good coupling conversions for His‐tagged proteins and some proteins with natural metal‐binding sites, however, it is not ideal as a guiding motif when pursuing the labelling of IgG molecules, as the labelling results in yields of typically 13–23 % . Likewise, proteins without metal‐binding sites cannot be addressed using the tris NTA guiding group.…”
Section: Figurementioning
confidence: 99%
“…Reactions between the guiding and the reactive strands should thereby be prevented. Initially, we tested the concept with a Rituximab antibody (a humanized IgG1 commercially known as Mabthera ® ) employing a 22 nt benzaldehyde‐modified reactive strand …”
Section: Figurementioning
confidence: 99%
“…In previous work from our group, [12] a trisnitrilotriacetic acid (NTA)-modified oligonucleotide (ODN) was used for DNA-templated [13] reactions toward metal-binding proteins. The trisNTAg roup showed very good coupling conversions for His-tagged proteins and some proteins with natural metalbinding sites,however, it is not ideal as aguiding motif when pursuing the labelling of IgG molecules,a st he labelling results in yields of typically 13-23 %.…”
mentioning
confidence: 99%